DECISION SUPPORT SYSTEM FOR SELECTING DIRECT CASH ASSISTANCE RECIPIENTS IN PANTON LABU VILLAGE USING A WEB-BASED AND MFEP METHOD - Zahidi Pratama; Wahyu Fuadi; Nunsina Nunsina (RADJA PUBLIKA, 2025)
The distribution of Direct Cash Assistance (BLT) often faces challenges related to data accuracy and fairness in recipient selection. This study aims to develop a web-based decision support system for selecting BLT recipients in Panton Labu Village using the Multi-Factor Evaluation Process (MFEP) method. The system was developed following the Waterfall software engineering model, utilizing PHP for programming and MySQL for database management. Data were collected through field observations, literature reviews, and interviews with village officials. The MFEP method evaluates prospective recipients based on six criteria: employment status, number of dependents, homeownership, building type, floor type, and monthly income. The system incorporates a Geographic Information System (GIS) feature to visualize applicants' home locations, with color-coded markers indicating eligibility. Testing on 120 data entries revealed that 34.2% (41 individuals) qualified for assistance using a minimum threshold score of 3.00. The system successfully automated calculation processes, enhanced transparency through digital mapping, and provided a user-friendly interface. This implementation demonstrates the effectiveness of the MFEP method in supporting objective, systematic, and targeted decision-making for social assistance programs at the village level